"Dear Fresher …" – How Online Questionnaires can Improve Learning and Teaching Statistics. (6th July 2015) - Bebermeier, Sarah; Nussbeck, Fridtjof W.; Ontrup, Greta
Lecturers teaching statistics are faced with several challenges supporting students' learning in appropriate ways. A variety of methods and tools exist to facilitate students' learning on statistics courses. The online questionnaires presented in this report are a new, slightly different computer-based tool: the central aim was to support students to master the course content and to provide the lecturer with continuous feedback about the students' difficulties and deficits. The aims of online questionnaires supporting teaching and learning of statistics are compared to aims of other computer-based and non-computerized methods and tools. Additionally, data from a first evaluation of the questionnaires is presented. In a first year psychology student's statistics course (bachelor program), students were offered the possibility of filling in an online questionnaire every time a specific theme had been taught. Out of the 126 first year students there were 28 who answered the online questionnaires regularly and 12 answered them sometimes. Those who answered the online questionnaires assessed them as helpful for their understanding of the course's content. The lecturer judged the online questionnaires as particular helpful for improving teaching and assessing performance deficits.